2017
DOI: 10.2337/db17-0116
|View full text |Cite
|
Sign up to set email alerts
|

Bone Regulates Browning and Energy Metabolism Through Mature Osteoblast/Osteocyte PPARγ Expression

Abstract: Peroxisome proliferator-activated receptor γ (PPARγ) is a master regulator of energy metabolism. In bone, it is known to regulate osteoblast differentiation and osteoclast activity. Whether PPARγ expression in bone cells, particularly osteocytes, regulates energy metabolism remains unknown. Here, we show that mature osteoblast/osteocyte-specific ablation of PPARγ in mice (γ/) alters body composition with age, namely, to produce less fat and more lean mass, and enhances insulin sensitivity and energy expenditur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 48 publications
(51 reference statements)
9
40
2
Order By: Relevance
“…These results indicate that ATP synthesis and glucose catabolism were considerably increased in the femoral tissues of the hyperthyroid rats. It has previously been found that bones play an essential role in whole-body glucose homeostasis, and bone remodelling is a dynamic ATP-consuming process that occurs via glucose catabolism [20-23]. T4 has been shown to accelerate the rates of oxygen consumption and heat production in various body tissues [7].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that ATP synthesis and glucose catabolism were considerably increased in the femoral tissues of the hyperthyroid rats. It has previously been found that bones play an essential role in whole-body glucose homeostasis, and bone remodelling is a dynamic ATP-consuming process that occurs via glucose catabolism [20-23]. T4 has been shown to accelerate the rates of oxygen consumption and heat production in various body tissues [7].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the question of which molecules link bone and glucose metabolism arises. Mouse studies have revealed that several osteokines, such as OCN, LCN2, BMP7 and sclerostin, actively participate in energy metabolism by modulation of glucose homeostasis, appetite and browning of adipose tissue. Meanwhile, the possible involvement of RANKL and NPY cannot be neglected.…”
Section: Bone As An Insulin Target Organ and Its Role In Glucose Homementioning
confidence: 99%
“…Osteocytes are the terminally differentiated osteoblasts and comprise nearly 95% of the cells residing in bone . Generally recognized as mechanical load‐sensing effectors, osteocytes are now known for their indispensable role in decreasing body weight upon increased loading and in mediating energy metabolism through secretory factors …”
Section: The Role Of Osteocyte‐secreted Molecules In Energy Metabolismmentioning
confidence: 99%
See 2 more Smart Citations